In Vivo Influenza Virus-Inhibitory Effects of the Cyclopentane Neuraminidase Inhibitor RWJ-270201 - Sidwell, Robert W. (American Society for Microbiology, 2001)
The cyclopentane influenza virus neuraminidase inhibitor RWJ-270201 was evaluated against influenza A/NWS/33 (H1N1), A/Shangdong/09/93 (H3N2), A/Victoria/3/75 (H3N2), and B/Hong Kong/05/72 virus infections in mice. Treatment was by oral gavage twice daily for 5 days beginning 4 h pre-virus exposure. The influenza virus inhibitor oseltamivir was run in parallel, and ribavirin was included in studies with the A/Shangdong and B/Hong Kong viruses. RWJ-270201 was inhibitory to all infections using doses as low as 1 mg/kg/day. Oseltamivir was generally up to 10-fold less effective than RWJ-270201. Ribavirin was also inhibitory but was less tolerated by the mice at the 75-mg/kg/day dose used. Disease-inhibitory effects included prevention of death, lessening of decline of arterial oxygen saturation, inhibition of lung consolidation, and reduction in lung virus titers. RWJ-270201 and oseltamivir, at doses of 10 and 1 mg/kg/day each, were compared with regard to their effects on daily lung parameters in influenza A/Shangdong/09/93 virus-infected mice. Maximum virus titer inhibition was seen on day 1, with RWJ-270201 exhibiting the greater inhibitory effect, a titer reduction of >10(4) cell culture 50% infective doses (CCID(50))/g. By day 8, the lung virus titers in mice treated with RWJ-270201 had declined to 10(1.2) CCID(50)/g, whereas titers from oseltamivir-treated animals were >10(3) CCID(50)/g. Mean lung consolidation was also higher in the oseltamivir-treated animals on day 8. Both neuraminidase inhibitors were well tolerated by the mice. RWJ-270201 was nontoxic at doses as high as 1,000 mg/kg/day. These data indicate potential for the oral use of RWJ-270201 in the treatment of influenza virus infections in humans.